Tailoring Optical Fields Emitted by Subwavelength Nanometric Sources - Bustos Marun, Raul Alberto (2014)
In this work, we study a simple way of controlling the emitted fields of subwavelength nanometric sources. The system studied consists of arrays of nanoparticles (NPs) embedded in optical active media. The key concept is the careful tuning of NP’s damping factors, which changes the eigenmode’s decay rates of the whole array. This inevitably leads, at long time, to a locking of relative phases and frequencies of individual localized-surfaces-plasmons (LSPs) and, thus, controls the emitted field. The amplitude of the LSP’s oscillations can be kept constant by embedding the system in optical active media. In the case of full loss compensation, this implies that not only the relative phases, but also the amplitudes of the LSPs remain fixed, leading us, additionally, to interpret the process as a new example of synchronization. The proposed approach can be used as a general way of controlling and designing the electromagnetic fields emitted by nanometric sources, which can find applications in optoelectronic, nanoscale lithography, and probing microscopy.